PRODUCTION PERFORMANCE OF BRONZE FEATHERBACK (Notopterus notopterus, Pallas 1769) REARED WITH DIFFERENT STOCKING DENSITIES AND TYPES OF FEED - Yulindra, Ade; Sukendi, Sukendi; Aryani, Netti (Asian Journal of Aquatic Sciences, 2022)
Bronze featherback is one of Indonesia’s endemic fish that has high economic value and has begun to decline in population in nature. There should be attempts at bronze featherback farming to maintain its existence in nature. The purpose of this study was to analyze the production performance, feed retention and glycogen accumulation of bronze featherback cultivated with stocking density and different types of feed. This study was conducted from May to August 2020 in Sungai Paku Village, Kampar Kiri sub-district, Kampar district. The experiment design used is a randomized complete design with two factors. Stocking density factor treatment consisting of 5, 10, and 15 fish/m3 and type of feed factor consists of trash fish and freshwater seashell meat feed. Bronze featherback was cultivated for 90 days. The fish was cultivated with 5% feed/day. Best result was in the stocking density of 5 fish/m3 and trash fish feed showed Absolute growth rate 50,05 g, Absolute length growth rate 11,48 cm, specific growth rate 2,83%, survival rate 86,7%, protein retention 68,68%, fat retention 34,11%, muscle glycogen 28,86 mg/g and liver glycogen 0,58 mg/g.